Endoscopic Removal of Skull Base Chordoma Type III through Single Skull Base Approach: Our Early Experience (Bangladesh Journal of Neurosurgery, 2019)
Introduction: Skull base chordomas present with headache, commonly VI cranial nerve palsy or sometimes with lower cranial nerve involvement.Sometimes in neglected case it presents with complete blindness and facial nerve palsy.Case presentation: A 60-year old man presented with headache,visual disturbance progressing to blindness and facial nerve palsy. At first, radiological imaging showed large tumor which eroded his clivus, sella floor and involved both cavernous carotid more on left side,both ethmoid sinus,middle cranial fossa entension with transdural extension posteriorly.Conclusion: Patients who present with complete blindness and facial nerve palsy, endoscopic excision in a single skull base approach of a skull base chordoma type III is challenging and who developed visual improvement following surgery, has been highlighted in this report.Bang. J Neurosurgery 2019; 9(1): 57-63